The U.S.‐South Korea Alliance: Local, Regional, and Global Dimensions. Issue 1 (16th January 2016) - Bong, Youngshik Daniel
Abstract : The U.S.‐South Korea military alliance has helped South Korea cope with key conditions that have threatened its sovereignty and national character. It has evolved into a security alliance that is mature, multidimensional, and comprehensive in terms of its main structure, operational scope, and mission. Domestic political conditions and public opinion in South Korea have been largely supportive of the bilateral security alliance. At the regional level, South Korea's anxiety regarding Japan's growing role in regional security matters has collided with its desire to transform the alliance to play a more effective role in the Asia‐Pacific region. The progressive nature of the threat of North Korea's weapons of mass destruction has introduced global objectives into the U.S.‐South Korea security alliance. Effectively coping with such "hybrid" threats from North Korea will remain the key challenge for the U.S.‐South Korea alliance in the future.